Karakterisasi Spektroskopi Raman pada Purifikasi Mixed Hydroxide Precipitate dari Baterai Lithium Bekas - Sedyatama, Deska Anggrait; Perdana, Indra; Sutijan, Sutijan (UM Purwokerto Press, 2023)
Electrical energy storage batteries are a form of this supporting technology. Lithium batteries are considered the most suitable battery technology for many types of electronic devices today. Waste of used batteries will also increase as LIB production increases. The recycling process is one way to dispose of used batteries because they contain high levels of heavy metals, which pose a significant risk. The most common treatment method for battery recycling is hydrometallurgy. The most important of the various hydrometallurgical steps is the leaching process. The mixed hydroxide precipitate (MHP) will be the product of the precipitation on the NMC metal. Na2SO4 is always an impurity present in MHP products. Therefore, the MHP still needs to be purified to achieve the highest possible purity so that it can be used as a cathode in battery manufacturing. Raman’s spectroscopic was used to analyze the characteristic of MHP purification with variation 30, 50, 70 and 90 oC.